Determinants of performance in 1,500-m runners - Ferri, A.; Adamo, S.; La Torre, A.; Marzorati, M.; Bishop, D. J.; Miserocchi, G. (European Journal of Applied Physiology, 2012)
Our aim was to investigate the relationship between physiological variables (not previously studied) and performance in elite 1,500-m runners. We assessed eight male athletes with an average personal best time of 233.3 ± 6.9 s (110% of the world record) for the 1,500-m race. Ventilatory measurements, maximal oxygen consumption (VO2max) maximal vastus lateralis muscle deoxygenation (d[deoxy(Hb+Mb)])max via near-infrared spectroscopy (NIRS), and maximal velocity (V max) were obtained during an incremental treadmill test. During subsequent constant-speed exercise at V max, we determined the time to exhaustion (Tlim), end-exercise blood lactate concentration ([La]bmax), VO2 and d[deoxy(Hb+Mb)] kinetics parameters. The mean VO2max [La]bmax and V max were 70.2 ± 3.9 mL/kg/min, 12.7 ± 2.4 mmol L-1, 21.5 ± 0.5 km/h, respectively. VO2 at V max showed a significant negative correlation with Tlim, whereas [La]bmax was positively correlated with Tlim. Race speed was found to significantly correlate with d[deoxy(Hb+Mb)]max (79% of maximal value obtained during a transient limb ischemia), d[deoxy(Hb+Mb)] slow component (22.9 ± 9.3% of total amplitude) and [La]bmax at V max. [La]bmax at V max was also significantly correlated with d[deoxy(Hb+Mb)] slow component, suggesting a greater release of oxygen from the hemoglobin due to the Bohr effect. We conclude that both the maximal capacity of muscle to extract O2 from the blood and the end-exercise blood lactate accumulation are important predictors of best performance in 1,500-m runners.